Classification of axial SpA based on positive imaging (radiographs and/or MRI of the sacroiliac joints) by local rheumatologists or radiologists versus central trained readers in the DESIR cohort. Issue 11 (24th June 2014) - van den Berg, Rosaline; Lenczner, Grégory; Thévenin, Fabrice; Claudepierre, Pascal; Feydy, Antoine; Reijnierse, Monique; Saraux, Alain; Rahmouni, Alain; Dougados, Maxime; van der Heijde, Désirée
Abstract : Objective: Investigating changes in patient classification (ASAS (Assessment of SpondyloArthritis international Society) axSpA criteria) based on evaluation of images of the sacro-iliac joints (MRI-SI and X-SI) by local and central readers. Methods: The DESIR cohort included patients with inflammatory back pain (IBP; ≥3 months, but <3 years), suggestive of axSpA. Local radiologists/rheumatologists (local-reading) and two central readers (central-reading) evaluated baseline images. Agreement regarding positive MRI (pos-MRI) between central readers and between local-reading and central-reading was calculated (κs). Number of patients classified differently (ASAS criteria) by using local-reading instead of central-reading was calculated. Results: Inter-reader agreement between the two central readers and between local-reading and central-reading was substantial (κ=0.73 and κ=0.70, respectively). In 89/663 MRI-SIs (13.4%) local-reading and central-reading disagreed; 38/223 patients (17.0%) with pos-MRI (local-reading) were negative by central-reading; 51/440 patients (11.6%) with neg-MRI (local-reading) were positive by central-reading. In 163/582 patients eligible for applying ASAS criteria (28.0%), local-reading and central-reading disagreed on positive imaging (MRI-SI and/or X-SI; κ=0.68). In 46/582 patients (7.9%) a different evaluation resulted in a different classification; 18/582 patients (3.1%) classified no-SpA (central-reading) were axSpA by local-reading; 28/582 patients (4.8%) classified axSpA (central-reading) were no-SpA by local-reading. Among axSpA patients (central-reading), 16/419 patients (3.8%) fulfilling imaging-arm by central-reading fulfilled clinical-arm by local-reading; 29/419 patients (6.9%) fulfilling clinical-arm by central-reading fulfilled also imaging-arm by local-reading. Conclusions: In patients with recent onset IBP, trained readers and local rheumatologists/radiologists agree well on recognising a pos-MRI. While disagreeing in 28% of the patients on positive imaging (MRI-SI and/or X-SI), classification of only 7.9% of the patients changed based on a different evaluation of images, showing the ASAS axSpA criteria's robustness.